The Human Resource Management Function and Perceptions of Organizational Performance - Supangco, Vivien T. (Philippine Management Review; Vol 9 (2001), 2016)
This study looked into the strategic management of the HR function in terms of the sophistication of its human resource management plan and its focus on practices that have greater strategic value.  Results from a sample of 71 firms in Metro Manila showed that there is a positive relationship between sophistication of the human resource management plan and perceptions of organizational performance and the degree to which firms undertake HR practices with greater strategic value.  In addition, it was also found that such transformational HR practices were positively associated with perceived organizational performance.  The resource-based theory of the firm was invoked to explain these relationships.